Early experience with influenza A H1N109 in an Australian intensive care unit - Leen, T.; Williams, Teresa; Campbell, L.; Chamberlain, J.; Gould, A.; McEntaggart, G.; Leslie, Gavin (Churchill Livingstone, 2010)
Summary: Influenza is a common seasonal viral infection that affects large numbers of people. In early 2009, many people were admitted to hospitals in Mexico with severe respiratory failure following an influenza-like illness, subtyped as H1N1. An increased mortality rate was observed. By June 2009, H1N1 was upgraded to pandemic status. In June-July, Australian ICUs were experiencing increased activity due to the influenza pandemic. While hospitals implemented plans for the pandemic, the particularly heavy demand to provide critical care facilities to accommodate an influx of people with severe respiratory failure became evident and placed a great burden on provision of these services. This paper describes the initial experience (June to mid September) of the pandemic from the nursing perspective in a single Australian ICU. Patients were noted to be younger with a higher proportion of women, two of whom were pregnant. Two patients had APACHE III comorbidity. Of the 31 patients admitted during this period, three patients died in ICU and one patient died in hospital. Aerosol precautions were initiated for all patients. The requirement for single room accommodation placed enormous demands for bed management in ICU. Specific infection control procedures were developed to deal with this new pandemic influenza.